2005
DOI: 10.1128/jcm.43.1.74-83.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Pneumococcal Colonization in Response to Pneumococcal Conjugate Vaccination in Children with Recurrent Acute Otitis Media

Abstract: A randomized double-blind trial with a 7-valent pneumococcal conjugate vaccine was conducted in The Netherlands among 383 children, aged 1 to 7 years, with a history of recurrent acute otitis media. No effect of vaccination on the pneumococcal colonization rate was found. However, a shift in serotype distribution was clearly observed (R. Veenhoven et al., Lancet 361:2189-2195, 2003). We investigated the molecular epidemiology of 921 pneumococcal isolates retrieved from both the pneumococcal vaccine (PV) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…It has also been reported that colonization with Staphylococcus aureus of healthy children is inversely correlated with colonization with vaccine-type S. pneumoniae (3,31,44,57). This negative correlation is not seen between S. aureus and non-vaccine-type S. pneumoniae.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…It has also been reported that colonization with Staphylococcus aureus of healthy children is inversely correlated with colonization with vaccine-type S. pneumoniae (3,31,44,57). This negative correlation is not seen between S. aureus and non-vaccine-type S. pneumoniae.…”
mentioning
confidence: 74%
“…Of even greater concern, however, is the increased incidence of colonization and disease caused by non-vaccine-type pneumococci (3,54,57), which had been predicted by prior studies using mathematical models (29,30). It has been observed that in a Native American population in Alaska, the continued use of the 7-valent vaccine has resulted in almost complete replacement disease caused by vaccine types not present in the 7-valent vaccine (54).…”
mentioning
confidence: 94%
“…Our data on pilus island distribution are comparable to the data in the published study by Margarit et al (2009), and the similarities are sufficient to confirm that the serotype and associated pilus island distribution in South Africa is similar to that reported in the USA and Europe, and based on this homogeneity of pilus island distribution, a pilusbased vaccine developed for these industrialized countries will have similar coverage in South Africa. What remains to be determined is whether pressure from such a vaccine can result in the emergence of strains that lack pilus islands as the dominant virulent types as has been witnessed for other pathogens, such as Streptococcus pneumoniae (Bogaert et al, 2005;Singleton et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Varios ensayos más han evaluado la eficacia de la VNC7v sola o seguida de la vacuna neumocócica polisacárida en la prevención de recurrencia de la otitis media aguda, encontrando ausencia de eficacia 67 o un efecto preventivo discreto [68][69][70] .…”
Section: Eficaciaunclassified
“…En resumen, los ensayos aleatorizados de la VNC7v, así como los de la vacuna ampliada nonavalente, demuestran que es altamente eficaz frente a ENI por serotipos vacunales 2-3,47,71-72 , de moderada eficacia frente a la neumonía 47,65,72 , y algo eficaz frente a la otitis media aguda 2,12,[67][68][69][70]73 .…”
Section: Eficaciaunclassified